Nonfatal Agricultural Injuries in Florida: Animal Production - Lucia Papadopulos; Cassandra Ward; Serap Gorucu (EDIS)
This publication examines nonfatal injuries and illnesses in the state of Florida’s animal production subsector. Written by Lucia Papadopulos, Cassandra Ward, and Serap Gorucu, and published by the UF/IFAS Department of Agricultural and Biological Engineering, September 2022.